(3GdNUGFUs - (3YKeGf Hf Lfj GdehUdj, CHh GdaJM, GHf Lfj,J (B392 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdYOd GdbOje hUdi Gddg Ydi eMeOq s
(3BNQgG (B:s
(3Je GdJYdjb hGdMeO ddg hUdi Gddg Ydi QShdgq s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B204 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B251 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B652s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs